A fantasia de atleta no imaginário de corredores amadores: análise do papel das marcas esportivas na construção da imagem de participantes de grupos de corrida - Lima, Renata Pereira (2007)
The main objective of this research was to describe and analyze the image that amateur runners, members of the runners´ team Run & Fun, in São Paulo, have of themselves: how they perceive themselves as runners and what are the values that characterize and unite them. An ethnographic research was conducted during one year in which the runners´ routine and their relationship among themselves and with the trainers were observed and described, as well as their clothes (the team´s uniform and the sneakers). Considering that there are beginner and initiate runners in the group, this research tried to identify if both kinds of runners share the same image or if beginner´s image is built by their companionship with initiate runners. The research also tried to identify the role that the main sneakers´ brands, Asics, Mizuno and Nike, play in the idealized runners´ image. Living together with these athletes during one year revealed that beginners and initiates do not share the same idealized image of being an amateur runner. Each of them create their own athlete´s fantasy . In other words, they use different symbols to be connected with running and with the runners´ team. In a sense, sneakers´ brands and runners´ teams are brands that have different meanings built up by the runners to create their athlete´s fantasies